Health Care Resource Utilization and Management of Chronic, Refractory Low Back Pain in the United States. Issue 20 (15th October 2020) - Spears, Charis A.; Hodges, Sarah E.; Kiyani, Musa; Yang, Zidanyue; Edwards, Ryan M.; Musick, Alexis; Park, Christine; Parente, Beth; Lee, Hui-Jie; Lad, Shivanand P.
Abstract : Supplemental Digital Content is available in the text